Digital feminist activism: Analyzing Jakarta Feminist as a collective identity, resources, network, information dissemination, and mobilization - Rifka Annisa (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
The use of social media for feminist activism in Indonesia has increased in decades. Some studies have mentioned digital feminist activism as the three intersectional relations of collective agenda, civic network, and digital infrastructure. To deepen, this study aims to analyze digital feminist activism works to organize collective identities, develop resources, coordinate networks, disseminate information, and mobilize social actors, in the case of Jakarta Feminist through a qualitative approach combined with social and textual network analysis. As a result, the Jakarta Feminist collective’s identity formed based on their identities, concerns, and defaces to the right of all Indonesian women, and other minorities group succeeded in developing resources in the form of moral, cultural, material, human, and network. Jakarta Feminist disseminated activism information by using social media features, and their members’ ties. Mobilized actors by conducting internal group planning, themes, and hashtags, boosted by social media personalities digital campaigns, individual and cross-organization. This study concluded that feminist digital activism running by the combination of their work in online and offline spheres. The cross-sectional interrelated of feminist activism to other issues, movements, and entities are interesting topics for future research.